THE POTENTIAL USE OF MINI WIND TURBINES AT SEKOLAH TINGGI ILMU PELAYARAN AS AN ALTERNATIVE RENEWABLE ELECTRICAL ENERGY SOURCE - Yudhiyono, Yudhiyono; MUDAKIR, MUDAKIR; ARIYANTO, ARIYANTO (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STIP Jakarta, 2023)
The need for electrical energy from year to year is getting bigger along with the increasing growth of population and industry, especially in big cities in Indonesia. The need for electrical energy in Indonesia still depends on Electrical Energy provided by the Perusahaan Listrik Negara (PLN). the main source of PLN's electrical energy is Fuel oil and Coal (50.01%). Sekolah Tinggi Ilmu Pelayaran as an educational institution seeks to support the government to reduce dependence on electrical energy produced with fossil fuels by seeking the potential of electrical energy sourced from renewable energy sources. One of the energies that has the potential as alternative energy is wind energy, where kinetic energy from the wind is utilized into electrical energy using wind turbines. For this reason, it is necessary to calculate the potential of wind energy as a renewable alternative energy at Sekolah Tinggi Ilmu Pelayaran